PERMIAN TETRAPOD ICHNOFACIES - Hunt A.P.; Lucas S.G. (My University, 2006)
Three fundamental terras in ichnology are: (1) assemblage, which is equivalent to an assemblage of body fossils; (2) ichnocoenosis, which is a trace fossil assemblage produced by a biological community that can be characterized by morphological criteria; (3) ichnofacies, which refers to recurrent ichnocoenoses that representa significant portion of Phanerozoic time. There are tive archetypal vertebrate ichnofacies for non-marine environments (Chelichnus, Grallator, Carichnium, Batrachichnus, Characichichnos) of which four are present in the Permian: (1) Chelichnus ichnofacies - Chelichnus ichnocoenosis; (2) Batraehichnus ichnofacies - Batrachichnus ichnocoenosis; (3) Brontopodus ichnofacies - Pachypes ichnocoenosis; (4) Characichichnos ichnofacies - Serpentichnus ichnocoenosis. The Chelichnus and Characichichnos ichnofacies occur throughout the Permian, the Batrachichnus ichnofacies is restricted to the Early Permian and the Brontopodus to the Middle to Late Permian. The Batrachichnus ichnocoenosis can be divided into the Ichniotherium sub-ichnocoenosis, Amphisauropus sub-ichnocoenosis and the Dimetropus sub-ichnocoenosis, which representa spectrum of non-marine environments from alluvial fan to tidal flat. © The Geological Society of London.
Keywords: Permian; Paleozoic::Permian; Палеозой::Пермская